Understanding telecommunications networks - Valdar, A. R. (The Institution of Engineering and Technology, 2017)
"A telecommunications network is an electronic system of links, nodes and the controls that govern their operations to allow voice and data transfer among users and devices. Examples of telecommunications networks are the telephone networks, computer networks and the Internet. Understanding Telecommunications Networks provides a comprehensive explanation of how various systems and technologies link together to construct fixed and mobile telecommunications networks and provide services. It uses straightforward language supported by block-schematic diagrams so that non-engineers and engineers alike can learn about the principles. This fully revised, updated and expanded second edition covers all aspects of today's networks, including how they are planned, formed and operated. After an introductory chapter on telephony, the book describes all of today's networks and considers how they link. Individual chapters then consider the principles, technologies and network structures relating to network components; transmission systems and networks; circuit switching systems and networks; signalling and control; data (packet) switching and routeing; and mobile systems and networks. The book concludes with a chapter designed to pull everything together, considering architecture, quality of service and performance, operations, network evolution and next generation networks. This is a companion volume to Understanding Telecommunications Business authored by Andy Valdar & Ian Morfett"--Provided by publisher
Keywords: Telecommunication systems.; Telecommunication.; elektronické knihy; electronic books